Negative electrode assembly for lithium metal battery, preparation method of negative electrode assembly and liquid metal battery
By setting a porous magnesium oxide isolation layer between the negative electrode of the liquid metal lithium battery and the solid electrolyte, the problems of unstable lithium ion transmission and short battery life in lithium batteries are solved, and higher battery performance and longer service life are achieved.
Patent Information
- Application Number
- CN202411868468.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
AI Technical Summary
During the operation of existing liquid metal lithium batteries, due to the interface resistance between the solid electrolyte and the electrode, the battery operation effect is affected, and liquid metal lithium is prone to corrode the solid electrolyte, resulting in a decrease in battery life.
A porous magnesium oxide isolation layer is used as part of the composite transport layer. By setting up a porous magnesium oxide isolation layer to avoid direct contact between molten lithium and solid electrolyte, a stable liquid lithium ion transport layer is built to ensure the transmission of lithium ions.
It realizes stable transmission of lithium ions, avoids the problem of excessive use of lithium salts, extends the cycle life of the battery, and improves the battery's Coulomb efficiency and rate performance.
Smart Images

Figure CN119674282A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium metal batteries and relates to a negative electrode assembly for a lithium metal battery, a preparation method thereof and a liquid metal battery. Background Art
[0002] Liquid metal batteries are usually composed of two layers of molten metal electrodes and a solid electrolyte in the middle, in which the solid electrolyte acts as the battery's separator and electrolyte for the transmission of lithium ions. Liquid metal batteries have the characteristics of large capacity, high energy density, low cost, and high efficiency. They also avoid the problems of traditional batteries such as dendrite growth that limit cycle life, have a long service life, and have good development prospects.
[0003] However, during the operation of existing batteries, there is interfacial resistance between the solid electrolyte and the electrode, which seriously affects the operation of the battery. In addition, liquid metal lithium easily comes into direct contact with the solid electrolyte, which in turn corrodes the solid electrolyte and reduces the battery life. In recent years, researchers usually add some low-melting-point lithium salts to isolate the liquid metal lithium from the electrolyte, but too little lithium salt cannot completely isolate it, and too much will affect the performance of the battery. At the same time, the high cost of lithium salts has slowed the development of liquid metal batteries. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a negative electrode assembly for a lithium metal battery, a preparation method thereof and a liquid metal battery, which constructs a stable liquid lithium ion transmission layer between the battery negative electrode and the solid electrolyte to ensure the transmission of lithium ions, and avoids direct contact between molten lithium and the solid electrolyte by providing a porous magnesium oxide isolation layer, reduces the use of lithium salts, and can also avoid the occurrence of short circuits.
[0005] To achieve this object, the present invention adopts the following technical solutions:
[0006] In a first aspect, the present invention provides a negative electrode assembly for a lithium metal battery, the negative electrode assembly comprising a negative electrode, a composite transport layer and a solid electrolyte arranged in sequence, the composite transport layer comprising a molten salt material, and a porous magnesium oxide isolation layer immersed in the molten salt material, the porosity of the porous magnesium oxide isolation layer on the side close to the negative electrode is less than the porosity of the porous magnesium oxide isolation layer on the side close to the solid electrolyte.
[0007] The porous magnesium oxide isolation layer used in the present invention has high mechanical strength and is not easy to break. It has a continuous pore structure inside, which can provide a transmission channel for molten salt ions and ensure the transmission speed of lithium ions. At the same time, it can physically isolate the generated metallic lithium and solid electrolyte, and improve the contact between the negative electrode and the solid electrolyte.
[0008] As a preferred technical solution of the present invention, the average porosity of the porous magnesium oxide isolation layer is 30% to 40%, for example, it can be 30%, 30.5%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% or 40%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0009] The present invention controls the average porosity of the porous magnesium oxide isolation layer within the above range. When the porosity is too large, the generated metallic lithium is easily embedded in the composite transport layer and cannot contact the negative electrode to form a dead lithium phenomenon, resulting in a decrease in the coulombic efficiency of the battery; when the porosity is too small, the molten salt is difficult to penetrate, resulting in a decrease in lithium ion channels, affecting the transmission speed of lithium ions, and resulting in a decrease in rate performance.
[0010] As a preferred technical solution of the present invention, the porous magnesium oxide isolation layer includes a first isolation layer and a second isolation layer stacked in sequence, the first isolation layer is connected to or close to the negative electrode, and the second isolation layer is connected to or close to the solid electrolyte; the porosity of the first isolation layer is less than the porosity of the second isolation layer.
[0011] The porous magnesium oxide isolation layer in the present invention adopts a layered design, which not only improves the rate cycle performance of the battery, but also helps to improve the coulombic efficiency of the battery.
[0012] Preferably, the thickness of the porous magnesium oxide isolation layer is 0.1 to 1 mm, for example, it can be 0.1 mm, 0.15 mm, 0.2 mm, 0.25 mm, 0.3 mm, 0.35 mm, 0.4 mm, 0.45 mm, 0.5 mm, 0.55 mm, 0.6 mm, 0.65 mm, 0.7 mm, 0.75 mm, 0.8 mm, 0.85 mm, 0.9 mm, 0.95 mm or 1 mm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] Preferably, the thickness of the first isolation layer is ≤0.2 mm.
[0014] The present invention controls the thickness of the porous magnesium oxide isolation layer within the above range, which not only ensures the mechanical strength of the isolation layer and avoids the problem of breakage during use, ensures that the porous magnesium oxide isolation layer can be immersed in the molten salt material by its own gravity, but also ensures the transmission distance of lithium ions, which is beneficial to improving the rate performance of the battery.
[0015] As a preferred technical solution of the present invention, the height of the molten salt material exceeding the porous magnesium oxide isolation layer is ≤0.1 mm.
[0016] That is, the molten salt material in the negative electrode assembly of the present invention does not have a porous magnesium oxide isolation layer, ensuring that its protruding height is ≤0.1 mm. On the one hand, the use of molten salt material is reduced and the production cost is reduced. On the other hand, the problem of increasing the ion transmission distance and reducing the battery rate performance due to the excessive height of the molten salt material is avoided.
[0017] Preferably, the molten salt material includes lithium salt and bromine salt.
[0018] Preferably, the molten salt material is a mixture of chlorine-containing lithium salt and bromine salt.
[0019] The molten salt material in the present invention has a relatively low melting point, and adopts a mixed molten salt of lithium salt and bromine salt, thereby improving its wettability with the porous magnesium oxide isolation layer, thereby increasing the transmission rate of lithium ions.
[0020] In a second aspect, the present invention provides a method for preparing a negative electrode assembly for a lithium metal battery as described in the first aspect, the preparation method comprising: preparing a porous magnesium oxide isolation layer using magnesium oxide as a raw material, covering the surface of a solid electrolyte with a molten salt material, immersing the porous magnesium oxide isolation layer into the interior of the molten salt material, and then disposing a negative electrode on the porous magnesium oxide isolation layer to obtain a negative electrode assembly.
[0021] As a preferred technical solution of the present invention, the method for preparing the porous magnesium oxide isolation layer comprises:
[0022] (1) Using a binder and a solvent to prepare a mixed colloid;
[0023] (2) mixing the magnesium oxide powder and the mixed colloid in a first mass ratio to obtain a first mixed powder, and then mixing the magnesium oxide powder and the mixed colloid in a second mass ratio to obtain a second mixed powder, wherein the first mass ratio is less than the second mass ratio;
[0024] (3) tableting the first mixed powder and sintering it once to obtain a magnesium oxide substrate;
[0025] (4) coating the second mixed powder on the surface of the magnesium oxide substrate and performing secondary sintering to obtain a porous magnesium oxide isolation layer.
[0026] It should be noted that the first mass ratio and the second mass ratio in the present invention both refer to the mass ratio of magnesium oxide powder to mixed colloid.
[0027] As a preferred technical solution of the present invention, the preparation process of the mixed colloid includes: mixing the binder and the solvent, heating and stirring, cooling to room temperature after the binder is dissolved, and obtaining the mixed colloid.
[0028] Preferably, the mass ratio of the binder to the solvent is 1:(12-18), for example, it can be 1:12, 1:12.5, 1:13, 1:13.5, 1:14, 1:14.5, 1:15, 1:15.5, 1:16, 1:16.5, 1:17, 1:17.5 or 1:18, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the binder comprises any one of polyvinyl alcohol, polyimide and sodium carboxymethyl cellulose or a combination of at least two of them, wherein typical but non-limiting combinations are: a combination of polyvinyl alcohol and polyimide, a combination of polyimide and sodium carboxymethyl cellulose, a combination of polyvinyl alcohol, polyimide and sodium carboxymethyl cellulose, and the like.
[0030] Preferably, the temperature of the heating treatment is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the stirring time is 1.5 to 4 h, for example, 1.5 h, 1.6 h, 2 h, 2.2 h, 2.5 h, 2.6 h, 2.8 h, 3 h, 3.3 h, 3.5 h, 3.8 h or 4 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] As a preferred technical solution of the present invention, the first mass ratio is (1.2-1.8):1, for example, it can be 1.2:1, 1.25:1, 1.3:1, 1.35:1, 1.4:1, 1.45:1, 1.5:1, 1.55:1, 1.6:1, 1.65:1, 1.7:1, 1.75:1 or 1.8:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, the second mass ratio is (2-2.5):1, for example, it can be 2:1, 2.1:1, 2.15:1, 2.2:1, 2.25:1, 2.3:1, 2.35:1, 2.4:1, 2.45:1 or 2.5:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0034] As a preferred technical solution of the present invention, the tabletting pressure is 8 to 12 MPa, for example, it can be 8 MPa, 8.5 MPa, 9 MPa, 9.5 MPa, 10 MPa, 10.5 MPa, 11 MPa, 11.5 MPa or 12 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the tabletting holding time is 300 to 480 s, for example, 300 s, 320 s, 350 s, 360 s, 380 s, 400 s, 420 s, 450 s, 460 s or 480 s, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] Preferably, the temperatures of the primary sintering and the secondary sintering are independently 800-1000°C, for example, 800°C, 820°C, 840°C, 850°C, 880°C, 900°C, 930°C, 950°C, 960°C, 980°C or 1000°C, but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] Preferably, the time for the primary sintering and the secondary sintering is independently 8 to 12 hours, for example, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] It should be noted that, in the present invention, the time for the first sintering is 8 to 12 hours, the time for the second sintering is 8 to 12 hours, and the time for the first sintering and the second sintering may be the same or different.
[0039] In a third aspect, the present invention provides a liquid metal battery, comprising a shell, in which a positive electrode region and a negative electrode region are arranged, the positive electrode region comprises a positive electrode material, the negative electrode region is provided with the negative electrode assembly for the lithium metal battery described in the first aspect, and the solid electrolyte is arranged on a side close to the positive electrode region and is sealed with the inner cavity wall of the shell.
[0040] The operating temperature of the liquid metal battery is 200-400°C, for example, it can be 200°C, 220°C, 230°C, 250°C, 280°C, 300°C, 330°C, 350°C, 360°C, 380°C or 400°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0041] The liquid metal battery provided by the present invention contains positive electrode materials in the positive electrode region and negative electrode molten salt materials in the negative electrode region. The negative electrode molten salt material is rich in lithium ions and can quickly transmit lithium ions, thereby effectively improving the coulombic efficiency of the battery and extending the battery cycle life.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] The negative electrode assembly for a lithium metal battery provided by the present invention constructs a stable liquid lithium ion transmission layer between the negative electrode of the battery and the solid electrolyte, thereby ensuring the transmission of lithium ions. The presence of the porous magnesium oxide isolation layer also avoids direct contact between molten lithium and the solid electrolyte, while reducing the use of lithium salts and avoiding the occurrence of short circuits, thereby improving the coulombic efficiency of the battery and extending the battery cycle life. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a schematic structural diagram of the liquid metal battery provided in Application Example 1 of the present invention.
[0045] Figure 2 This is a charge and discharge curve diagram of the liquid metal battery provided in Application Example 1 of the present invention.
[0046] Figure 3 This is a charge and discharge curve diagram of the liquid metal battery provided in comparative application example 1 of the present invention.
[0047] Among them, 100-negative electrode; 200-inner liner ring; 300-porous magnesium oxide isolation layer; 400-solid electrolyte; 500-negative electrode area; 600-positive electrode area; 700-shell. DETAILED DESCRIPTION
[0048] It should be understood that, in the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0049] It should be noted that in the description of the present invention, unless otherwise clearly specified and limited, the terms "disposed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood by specific circumstances.
[0050] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.
[0051] In a specific embodiment, the present invention provides a negative electrode assembly for a lithium metal battery, comprising a negative electrode, a composite transmission layer and a solid electrolyte arranged in sequence, the composite transmission layer comprising a molten salt material, and a porous magnesium oxide isolation layer immersed in the molten salt material, the porosity of the porous magnesium oxide isolation layer close to the negative electrode side surface is less than the porosity of the porous magnesium oxide isolation layer close to the solid electrolyte side surface, that is, it has a layered pore distribution, which can simultaneously ensure the rate performance and coulomb efficiency of the battery. The negative electrode is not in direct contact with the solid electrolyte, and a porous magnesium oxide isolation layer is arranged in the middle, and lithium ions are transmitted by embedding the molten salt in its pores to achieve indirect contact between the negative electrode and the solid electrolyte.
[0052] The negative electrode in the present invention is a conductive material that does not react and dissolve with metallic lithium at high temperatures, including but not limited to stainless steel, nickel, iron nickel, graphene, etc. well known to those skilled in the art. The negative electrode specifically includes a negative electrode column and a negative electrode current collector connected in sequence, and the negative electrode current collector is connected to the porous magnesium oxide isolation layer. The present invention does not specifically limit the structure, morphology and size of the negative electrode column and the negative electrode current collector. Those skilled in the art can select or cut a suitable structure according to the actual required battery configuration. The connection method between the negative electrode column and the negative electrode current collector can be indirect connection using fixed welding or connectors commonly used in the art, or an integrated molding structure can be used, and the present invention does not specifically limit this.
[0053] The porous magnesium oxide isolation layer of the present invention has a continuous pore structure, and the porosity on both sides is different from each other, the average porosity is 30% to 40%, and the pores can accommodate more molten salts, which is beneficial to the transmission speed of lithium ions, and is easy to prepare and has high mechanical strength. In addition, it also avoids the lithium generated by the pore size being too large to be embedded in the pores, and the dead lithium phenomenon is formed due to the lack of contact with the current collector, resulting in a decrease in the coulombic efficiency of the battery.
[0054] Furthermore, the porous magnesium oxide isolation layer includes a first isolation layer and a second isolation layer stacked in sequence, the first isolation layer is connected to or close to the negative electrode, the second isolation layer is connected to or close to the solid electrolyte, and the porosity of the first isolation layer is less than the porosity of the second isolation layer. The porous magnesium oxide isolation layer in the present invention is a layered structure, the materials of the first isolation layer and the second isolation layer are both magnesium oxide, the low porosity first isolation layer ensures the coulombic efficiency of the battery, and the high porosity second isolation layer ensures that the battery has a higher rate performance.
[0055] The porous magnesium oxide isolation layer is made of an inert material that is stable to metallic lithium and has a thickness of 0.1 to 1 mm, which ensures its mechanical strength while avoiding an increase in the migration path of lithium ions. Furthermore, the thickness of the first isolation layer is ≤ 0.2 mm.
[0056] The present invention does not specifically limit the material of the solid electrolyte, and any solid electrolyte material known to those skilled in the art may be used, including but not limited to lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium aluminum titanium phosphate, lithium lanthanum titanium oxide, etc.
[0057] The height of the molten salt material exceeding the porous magnesium oxide isolation layer in the present invention is ≤0.1 mm, which not only reduces the usage of the molten salt material, but also shortens the transmission distance of lithium ions, which is beneficial to improving the rate performance of the battery.
[0058] The molten salt material has the characteristics of being stable to metallic lithium, rich in lithium ions, and capable of rapidly transmitting lithium ions, and specifically includes lithium salt and bromine salt, with a melting point of 200-400° C. Since magnesium oxide is an inert material, its wettability with molten salt is poor, which is not conducive to the transmission rate of lithium ions. The present invention uses a mixed molten salt of lithium salt and bromine salt as the molten salt material of the negative electrode component, which can improve its wettability with magnesium oxide, especially the wettability between the molten salt material and the porous magnesium oxide isolation layer with a porosity range of 30% to 40%, thereby improving the rate performance of the battery. Exemplarily, the molten salt material includes but is not limited to LiI-CsBr (mass fraction ratio of 66%:34%), LiCl-KBr (mass fraction ratio of 58%:42%), LiCl-LiBr-KBr (mass fraction ratio of 12.1%:36.5%:51.4%), LiBr-KBr (mass fraction ratio of 60%:40%), LiF-LiBr-LiI (mass fraction ratio of 13%:34%:53%), LiF-LiBr-KBr (mass fraction ratio of 2.5%: 63.5%: 34%), LiCl-KBr-CsCl (mass fraction ratio of 57.5%: 13.3%: 29.2%), LiBr-KBr-CsBr (mass fraction ratio of 39.08%: 18.17%: 42.75%) and LiCl-KBr-CsBr (mass fraction ratio of 39.08%: 18.17%: 42.75%). Preferably, the molten salt material is a mixture of chlorine-containing lithium salt and bromine salt.
[0059] In another specific embodiment, the present invention provides a method for preparing a negative electrode assembly for a lithium metal battery according to a specific embodiment, the preparation method comprising:
[0060] S1: preparing a porous magnesium oxide isolation layer using magnesium oxide as a raw material;
[0061] S2: Covering the surface of the solid electrolyte with a molten salt material, and immersing the porous magnesium oxide isolation layer into the interior of the molten salt material;
[0062] S3: Then, the negative electrode is disposed on the porous magnesium oxide isolation layer to obtain a negative electrode assembly.
[0063] In some embodiments, the method for preparing the porous magnesium oxide isolation layer comprises:
[0064] (1) Using a binder and a solvent to prepare a mixed colloid;
[0065] (2) mixing the magnesium oxide powder and the mixed colloid in a mass ratio of (1.2 to 1.8):1 to obtain a first mixed powder, and then mixing the magnesium oxide powder and the mixed colloid in a mass ratio of (2 to 2.5):1 to obtain a second mixed powder;
[0066] (3) using the first mixed powder to press the tablet under a pressure of 8 to 12 MPa, and maintaining the pressure for 300 to 480 seconds, and sintering again to obtain a magnesium oxide substrate with a thickness of less than 1 mm, wherein the temperature of the first sintering is 800 to 1000° C., and the time is 8 to 12 hours;
[0067] (4) coating the second mixed powder on the surface of the magnesium oxide substrate and performing secondary sintering to obtain a porous magnesium oxide isolation layer, wherein the secondary sintering temperature is 800-1000° C. and the time is 8-12 hours.
[0068] Compared with the traditional in-situ sintering molding process, the porous isolation layer prepared by the preparation method provided by the present invention has uniform pores, is easy to control process parameters, and is more conducive to ensuring the transmission speed of lithium ions.
[0069] In some embodiments, the preparation process of the mixed colloid includes: mixing the binder and the solvent in a mass ratio of 1: (12 to 18), heating at 80 to 90° C., stirring for 1.5 to 4 hours, and cooling to room temperature after the binder is dissolved to obtain the mixed colloid.
[0070] Wherein, the binder includes any one of polyvinyl alcohol, polyimide and sodium carboxymethyl cellulose or a combination of at least two thereof; and the solvent may be water.
[0071] The mass proportion of the mixed colloid in the first mixed powder of the present invention is greater than the mass proportion of the mixed colloid in the second mixed powder, and after sintering, the porosity of the magnesium oxide substrate is greater than the porosity of the second mixed powder coated on its surface. When immersed in the molten salt material, the porous magnesium oxide isolation layer is close to the negative electrode from the side surface coated with the second mixed powder.
[0072] After the porous magnesium oxide isolation layer described in the present invention is immersed in the molten salt material, it sinks due to the action of gravity. At the same time, under the pressure of the negative electrode, the porous magnesium oxide isolation layer is close to the solid electrolyte. The lithium ions in the molten salt material are attached to the pores of the porous magnesium oxide isolation layer and are only transmitted through the pores of the porous magnesium oxide isolation layer, thereby avoiding direct contact between the molten lithium and the solid electrolyte.
[0073] In another specific embodiment, the present invention provides a liquid metal battery, which includes a shell, in which a positive electrode region and a negative electrode region are arranged, the positive electrode region includes a positive electrode material, and the negative electrode region is provided with a negative electrode assembly for a lithium metal battery as described in a specific embodiment, and the solid electrolyte is arranged on a side close to the positive electrode region and is sealed with the inner cavity wall of the shell.
[0074] The shell of the present invention is made of a material resistant to molten salt corrosion, and can be made of materials familiar to those skilled in the art, such as ceramics or stainless steel. The present invention does not specifically limit the structure and size of the shell, and those skilled in the art can adjust it according to actual battery requirements. In addition, depending on the material of the different shells, those skilled in the art can set a lining in the shell to insulate the inner wall of the shell from the negative electrode assembly.
[0075] The positive electrode region of the present invention contains positive electrode materials, and the positive electrode materials include lithium-containing halide salts, lithium ion conductive additives and electronic conductive additives, etc., all of which are materials well known to those skilled in the art. Exemplarily, the lithium-containing halide salts include but are not limited to any one or a combination of at least two of lithium chloride, lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, and lithium trifluoromethanesulfonate; the lithium ion conductive additives include but are not limited to LiAlCl4 and / or LiZnCl4; the electronic conductive additives include but are not limited to any one or a combination of at least two of copper powder, brass powder, zinc or carbon black.
[0076] The liquid metal battery of the present invention uses the solid electrolyte of the negative electrode assembly to divide the positive electrode area and the negative electrode area, and the porous magnesium oxide isolation layer is arranged between the negative electrode and the solid electrolyte to avoid direct contact between the two; the negative electrode area is filled with molten salt material. When the battery is running, the molten salt material does not cover the porous magnesium oxide isolation layer, and lithium ions are transmitted inside the pores of the porous magnesium oxide isolation layer, thereby avoiding direct contact between molten lithium and the solid electrolyte, and reducing the use of lithium salt. The operating temperature of the liquid metal battery is 200-400°C.
[0077] In addition, the inner wall of the shell is sealed to the solid electrolyte, and the sealing method includes but is not limited to glass sealing and inorganic salt sealing. When a lining is provided in the shell, it should be ensured that the lining is also sealed to the shell and the solid electrolyte.
[0078] The liquid metal battery of the present invention must include battery covers, seals, connectors and fasteners necessary to achieve a complete process, but the above content does not belong to the main invention of the present invention. Technical personnel in this field can add layouts on their own based on the process flow and equipment structure selection. The present invention does not make special requirements and specific limitations on this.
[0079] Preparation Example 1
[0080] This preparation example provides a method for preparing a porous magnesium oxide isolation layer, which specifically includes the following steps:
[0081] (1) polyvinyl alcohol 2000 and water are mixed in a mass ratio of 1:15, and heated at 90° C. while stirring for 2 hours. After the binder is dissolved, the mixture is cooled to room temperature to obtain a mixed colloid for standby use;
[0082] (2) mixing the magnesium oxide powder and the mixed colloid in a mass ratio of 1.5:1 to obtain a first mixed powder, and then mixing the magnesium oxide powder and the mixed colloid in a mass ratio of 2:1 to obtain a second mixed powder;
[0083] (3) taking out 0.2 g of the first mixed powder and putting it into a powder tablet press, pressing it under a pressure of 10 MPa, and maintaining the pressure for 300 seconds, and then putting it into a muffle furnace for primary sintering to obtain a magnesium oxide substrate with a diameter of 18 mm, wherein the primary sintering temperature is 850° C., the time is 10 hours, and the thickness of the magnesium oxide substrate is measured to be 0.7 mm;
[0084] (4) coating the second mixed powder on the surface of the magnesium oxide substrate, and placing it in a muffle furnace for secondary sintering to obtain a porous magnesium oxide isolation layer, wherein the coating thickness is 0.15 mm, the secondary sintering temperature is 850° C., and the time is 10 h.
[0085] The porous magnesium oxide isolation layer prepared in this preparation example has a thickness of 0.8 mm and an average porosity of 37%.
[0086] Preparation Example 2
[0087] This preparation example provides a method for preparing a porous magnesium oxide isolation layer, which specifically includes the following steps:
[0088] (1) polyvinyl alcohol 2000 and water are mixed in a mass ratio of 1:12, and heated at 80° C. while stirring for 4 hours. After the binder is dissolved, the mixture is cooled to room temperature to obtain a mixed colloid for standby use;
[0089] (2) mixing the magnesium oxide powder and the mixed colloid in a mass ratio of 1.8:1 to obtain a first mixed powder, and then mixing the magnesium oxide powder and the mixed colloid in a mass ratio of 2.2:1 to obtain a second mixed powder;
[0090] (3) taking out 0.2 g of the first mixed powder and putting it into a powder tablet press, pressing it at a pressure of 12 MPa, and maintaining the pressure for 480 seconds, and then putting it into a muffle furnace for primary sintering to obtain a magnesium oxide substrate with a diameter of 18 mm, wherein the primary sintering temperature is 900° C., the time is 8 hours, and the thickness of the magnesium oxide substrate is measured to be 0.5 mm;
[0091] (4) coating the second mixed powder on the surface of the magnesium oxide substrate, and placing it in a muffle furnace for secondary sintering to obtain a porous magnesium oxide isolation layer, wherein the coating thickness is 0.18 mm, the secondary sintering temperature is 900° C., and the time is 8 h.
[0092] The porous magnesium oxide isolation layer prepared in this preparation example has a thickness of 0.6 mm and an average porosity of 34%.
[0093] Preparation Example 3
[0094] This preparation example provides a method for preparing a porous magnesium oxide isolation layer, which specifically includes the following steps:
[0095] (1) polyvinyl alcohol 2000 and water are mixed in a mass ratio of 1:18, and heated at 90° C. while stirring for 1.5 hours. After the binder is dissolved, the mixture is cooled to room temperature to obtain a mixed colloid for standby use;
[0096] (2) mixing the magnesium oxide powder and the mixed colloid in a mass ratio of 1.8:1 to obtain a first mixed powder, and then mixing the magnesium oxide powder and the mixed colloid in a mass ratio of 2.5:1 to obtain a second mixed powder;
[0097] (3) taking out 0.2 g of the first mixed powder and putting it into a powder tablet press, pressing it at a pressure of 8 MPa, and maintaining the pressure for 400 seconds, and then putting it into a muffle furnace for primary sintering to obtain a magnesium oxide substrate with a diameter of 18 mm, wherein the primary sintering temperature is 1000° C., the time is 8 hours, and the thickness of the magnesium oxide substrate is measured to be 0.45 mm;
[0098] (4) coating the second mixed powder on the surface of the magnesium oxide substrate, and placing it in a muffle furnace for secondary sintering to obtain a porous magnesium oxide isolation layer, wherein the coating thickness is 0.1 mm, the secondary sintering temperature is 1000° C., and the time is 8 h.
[0099] The porous magnesium oxide isolation layer prepared in this preparation example has a thickness of 0.5 mm and an average porosity of 35%.
[0100] Preparation Example 4
[0101] This preparation example provides a method for preparing a porous magnesium oxide isolation layer. The difference from Preparation Example 1 is that the coating thickness in step (4) is 1 mm, and the remaining preparation steps and process parameters are the same as those in Preparation Example 1.
[0102] The porous magnesium oxide isolation layer prepared in this preparation example has a thickness of 1.4 mm and an average porosity of 39%.
[0103] Preparation Example 5
[0104] This preparation example provides a method for preparing a porous magnesium oxide isolation layer, which specifically includes the following steps:
[0105] (1) polyvinyl alcohol 2000 and water are mixed in a mass ratio of 1:15, and heated at 90° C. while stirring for 2 hours. After the binder is dissolved, the mixture is cooled to room temperature to obtain a mixed colloid for standby use;
[0106] (2) mixing the magnesium oxide powder and the mixed colloid in a mass ratio of 1.5:1 to obtain a first mixed powder;
[0107] (3) 0.2 g of the first mixed powder was taken out and put into a powder tablet press, and tableted at a pressure of 8 MPa, and the pressure was maintained for 300 seconds, and then put into a muffle furnace for a sintering to obtain a magnesium oxide substrate with a diameter of 18 mm, wherein the primary sintering temperature was 850° C. and the time was 10 hours.
[0108] The thickness of the magnesium oxide substrate prepared in this preparation example is 0.7 mm, and the average porosity is 40%.
[0109] Preparation Example 6
[0110] This preparation example provides a method for preparing a porous magnesium oxide isolation layer. The difference from Preparation Example 5 is that in step (2), the mass ratio of magnesium oxide powder to mixed colloid is 1:1, and the remaining preparation steps and process parameters are the same as those in Preparation Example 5.
[0111] The porous magnesium oxide isolation layer prepared in this preparation example has a thickness of 0.7 mm and an average porosity of 50%.
[0112] Preparation Example 7
[0113] This preparation example provides a method for preparing a porous magnesium oxide isolation layer. The difference from Preparation Example 5 is that in step (2), the mass ratio of magnesium oxide powder to mixed colloid is 3:1, and the remaining preparation steps and process parameters are the same as those in Preparation Example 5.
[0114] The porous magnesium oxide isolation layer prepared in this preparation example has a thickness of 0.7 mm and an average porosity of 20%.
[0115] Preparation Example 8
[0116] This preparation example provides a method for preparing a porous magnesium oxide isolation layer, which differs from Preparation Example 1 in that: in step (2), the mass ratio of magnesium oxide powder to mixed colloid in the first mixed powder is 2:1, and the mass ratio of magnesium oxide powder to mixed colloid in the second mixed powder is 1.5:1. The remaining preparation steps and process parameters are the same as those in Preparation Example 1.
[0117] Example 1
[0118] This embodiment provides a negative electrode assembly, including a negative electrode, a composite transmission layer and a solid electrolyte arranged in sequence. The composite transmission layer includes a molten salt material and an isolation layer immersed in the molten salt material, wherein the isolation layer adopts the porous magnesium oxide isolation layer prepared in Preparation Example 1.
[0119] The manufacturing method of the negative electrode assembly provided in this embodiment includes: providing LLZTO as a solid electrolyte, and covering the surface of the solid electrolyte with a molten salt material LiCl-LiBr-KBr-CsBr (mass fraction of 10.15%: 31.54%: 13.93%: 44.38%), immersing a porous magnesium oxide isolation layer into the interior of the molten salt material, with the side with high porosity close to the solid electrolyte, so that the height of the molten salt material submerged in the porous magnesium oxide isolation layer is 0.05 mm; welding a stainless steel current collector to one end of a stainless steel pole, cutting it into a size suitable for the negative electrode according to the morphology of the negative electrode structure in the battery mold, and then setting the negative electrode on the porous magnesium oxide isolation layer to obtain a negative electrode assembly.
[0120] Example 2
[0121] This embodiment provides a negative electrode assembly, which is different from Example 1 in that the isolation layer adopts the porous magnesium oxide isolation layer in Preparation Example 2, and the rest of the structure and preparation steps are the same as those in Example 1.
[0122] Example 3
[0123] This embodiment provides a negative electrode assembly, which is different from Example 1 in that the isolation layer adopts the porous magnesium oxide isolation layer in Preparation Example 3, and the rest of the structure and preparation steps are the same as those in Example 1.
[0124] Example 4
[0125] This embodiment provides a negative electrode assembly, which differs from Embodiment 1 in that the molten salt material used is LiCl-LiBr-KBr (mass fraction ratio is 12.1%:36.5%:51.4%), and the rest of the structure and preparation steps are the same as those of Embodiment 1.
[0126] Example 5
[0127] This embodiment provides a negative electrode assembly, which is different from Embodiment 1 in that the molten salt material adopts LiBr-KBr (mass fraction ratio is 60%:40%), and the rest of the structure and preparation steps are the same as those of Embodiment 1.
[0128] Example 6
[0129] This embodiment provides a negative electrode assembly, which is different from Embodiment 1 in that the molten salt material adopts LiBr-KBr-CsBr (mass fraction ratio is 39.08%:18.17%:42.75%), and the rest of the structure and preparation steps are the same as those of Embodiment 1.
[0130] Example 7
[0131] This embodiment provides a negative electrode assembly, which is different from Embodiment 1 in that the molten salt material adopts LiF-LiBr-KBr (mass fraction ratio is 2.5%:63.5%:34%), and the rest of the structure and preparation steps are the same as those of Embodiment 1.
[0132] Example 8
[0133] This embodiment provides a negative electrode assembly, which is different from Embodiment 1 in that the molten salt material adopts LiI-CsI (mass fraction ratio is 66%:34%), and the rest of the structure and preparation steps are the same as those of Embodiment 1.
[0134] Example 9
[0135] This embodiment provides a negative electrode assembly, which is different from Embodiment 1 in that the molten salt material adopts LiCl-KCl (mass fraction ratio is 58%:42%), and the rest of the structure and preparation steps are the same as those of Embodiment 1.
[0136] Comparative Example 1
[0137] This comparative example provides a negative electrode assembly, which is different from Example 1 in that a porous magnesium oxide isolation layer is not provided, and the rest of the structure and preparation method are the same as those of Example 1.
[0138] Comparative Example 2
[0139] This comparative example provides a negative electrode assembly, which is different from Example 1 in that the isolation layer adopts the porous magnesium oxide isolation layer in Preparation Example 4, and the remaining structure and preparation steps are the same as those in Example 1.
[0140] Comparative Example 3
[0141] This comparative example provides a negative electrode assembly, which is different from Example 1 in that the isolation layer adopts the porous magnesium oxide isolation layer in Preparation Example 5, and the rest of the structure and preparation steps are the same as those in Example 1.
[0142] Comparative Example 4
[0143] This comparative example provides a negative electrode assembly, which is different from Example 1 in that the isolation layer adopts the porous magnesium oxide isolation layer in Preparation Example 6, and the remaining structure and preparation steps are the same as those in Example 1.
[0144] Comparative Example 5
[0145] This comparative example provides a negative electrode assembly, which is different from Example 1 in that the isolation layer adopts the porous magnesium oxide isolation layer in Preparation Example 7, and the rest of the structure and preparation steps are the same as Example 1.
[0146] Comparative Example 6
[0147] This comparative example provides a negative electrode assembly, which differs from Example 1 in that the porous magnesium oxide isolation layer is replaced by carbon cloth, and the rest of the structure is the same as that of Example 1.
[0148] Comparative Example 7
[0149] This comparative example provides a negative electrode assembly, which differs from Example 1 in that the porous magnesium oxide isolation layer is replaced by foamed iron, and the rest of the structure is the same as that of Example 1.
[0150] Comparative Example 8
[0151] This comparative example provides a negative electrode assembly, which is different from Example 1 in that the isolation layer adopts the porous magnesium oxide isolation layer in Preparation Example 8, and the remaining structure and preparation steps are the same as those in Example 1.
[0152] Comparative Example 9
[0153] This comparative example provides a negative electrode assembly, which is different from Example 1 in that the height of the molten salt material not exceeding the porous magnesium oxide isolation layer is 0.3 mm, and the remaining structures and preparation steps are the same as those of Example 1.
[0154] Application Example 1
[0155] This application example provides a liquid metal battery, such as Figure 1As shown, a shell 700 made of ceramic material is included, and a positive electrode area 600 and a negative electrode area 500 are arranged in the shell 700, and a negative electrode assembly provided in Example 1 is arranged in the negative electrode area 500. The solid electrolyte 400 of the negative electrode assembly is arranged on a side close to the positive electrode area 600 and is sealed with the inner cavity wall of the shell 700. An inner liner ring 200 is also provided in the negative electrode area 500, which is sealed with the inner cavity wall of the shell 700, and a receiving cavity is formed between the inner liner ring 200 and the solid electrolyte 400 for placing the negative electrode 100 and the composite transmission layer. The negative electrode column extends out of the shell 700, and the negative electrode current collector presses the porous magnesium oxide isolation layer 300 in the composite transmission layer. The positive electrode area 600 is filled with a positive electrode material, and the positive electrode material is a mixture of LiCl, LiAlCl4 and brass powder.
[0156] Application Examples 2 to 9
[0157] The present invention uses the negative electrode assemblies of Examples 2 to 9 to prepare 2Ah liquid metal batteries, which are different from Application Example 1 only in the negative electrode assembly, and the rest of the specific structures and materials are the same as those of Application Example 1.
[0158] Then, at a current density of 50 mA / cm 2 The coulombic efficiency and rate performance of the liquid metal battery provided by Application Examples 1 to 9 are tested below, and the results are shown in Table 1.
[0159] Table 1
[0160]
[0161]
[0162] As can be seen from Table 1, the liquid metal battery made of the negative electrode assembly provided in Examples 1 to 4 has a high coulombic efficiency and rate performance. The coulombic efficiency of the battery using the negative electrode assembly of Examples 5 to 7 is high, but the rate performance is lower than that of Examples 1 to 4. This is mainly because the molten salt material used in Examples 1 to 4 is a mixture of chlorine-containing lithium salt and bromine salt, which has a better effect on improving the wettability of the porous magnesium oxide isolation layer, thereby improving the rate performance of the battery. The rate performance of the liquid battery using Examples 8 and 9 is further reduced, indicating that when other salt mixtures are used as molten salt materials, their wettability with the porous magnesium oxide isolation layer is lower than that using a mixture of lithium salt and bromine salt as the molten salt material.
[0163] Comparative application example 1
[0164] This comparative application example provides a liquid metal battery, which is different from Application Example 1 in that the negative electrode assembly adopts the negative electrode assembly provided in Comparative Example 1, and the rest of the specific structures and materials are the same as those in Application Example 1.
[0165] Comparative Application Examples 2 to 9
[0166] The present invention also uses the negative electrode assemblies of Comparative Examples 2 to 9 to prepare 2Ah liquid metal batteries, which are different from Application Example 1 only in the negative electrode assembly, and the rest of the specific structures and materials are the same as those of Application Example 1.
[0167] Then, at a current density of 50 mA / cm 2 The coulombic efficiency and rate performance of the liquid metal battery prepared using the negative electrode components provided in Comparative Application Examples 1 to 9 were tested under the following conditions, and the results are shown in Table 2.
[0168] Table 2
[0169] serial number Coulomb efficiency (%) Rate performance (C) Application Example 1 99 0.05 Comparative application example 1 80 0.05 Comparative Application Example 2 98 0.03 Comparative Application Example 3 92 0.04 Comparative Application Example 4 81 0.05 Comparative Application Example 5 97 0.01 Comparative Application Example 6 78 0.03 Comparative Application Example 7 82 0.03 Comparative Application Example 8 85 0.03 Comparative Application Example 9 99 0.03
[0170] The present invention also tests the charging and discharging operation of the liquid metal battery provided in Example 1 and Comparative Application Example 1 to obtain the charging and discharging curves thereof. Figure 2 As shown in FIG. 1 , the liquid metal battery provided in Application Example 1 can still be normally charged and discharged within a running time of 240 hours; while the charge and discharge curve of the liquid metal battery in Application Example 1 is shown in FIG. Figure 3 As shown in the figure, the battery short-circuited after only 120 hours of operation. This is because the porous magnesium oxide isolation layer in Application Example 1 achieves physical isolation between the negative electrode and the solid electrolyte, avoiding direct contact between the molten lithium and the solid electrolyte, thereby preventing the occurrence of a short circuit. In addition, the liquid metal battery in Application Example 1 short-circuited, making its coulombic efficiency lower than that of the liquid metal battery provided in Application Example 1.
[0171] It can be seen from Table 2 that compared with the negative electrode assembly of Example 1, the rate performance of the liquid metal battery made using Comparative Example 2 is reduced. This is because the overall thickness of the porous magnesium oxide isolation layer and the thickness of the coating layer used in Comparative Example 2 are too large, which generally increases the transmission distance of lithium ions and leads to a decrease in rate performance.
[0172] Compared with Application Example 1, the liquid metal batteries made of the negative electrode components provided in Comparative Examples 3 to 5 cannot simultaneously guarantee high coulombic efficiency and rate performance. This is mainly because the porous magnesium oxide isolation layer used in Application Example 1 has a layered pore structure and ensures a porosity of 30% to 40%, which can not only ensure the transmission speed of lithium ions, but also avoid the occurrence of dead lithium and other situations that reduce coulombic efficiency, thereby improving the overall operation effect of the battery.
[0173] Compared with Application Example 1, the coulombic efficiency and rate performance of the liquid metal battery made of the negative electrode assembly provided by Comparative Examples 6 and 7 are also reduced, which is caused by the different porous isolation layer materials used. The porosity of carbon cloth and foamed iron is relatively large, and metallic lithium is easily embedded inside to form dead lithium, or metallic lithium passes through the pores and directly contacts the solid electrolyte, which is easy to corrode the electrolyte. In addition, after the carbon cloth is infiltrated with molten salt, it is easy to deform and move, and its internal pore structure will also change, resulting in unstable battery operation. Foamed iron is easy to float in more molten salt, and has poor wettability with metallic lithium in a small amount of molten salt, which will affect the operation of the battery.
[0174] It is not difficult to see from Table 2 that the coulombic efficiency and rate performance of the liquid battery made using the negative electrode assembly provided in Comparative Example 8 are lower than those in Application Example 1, which is mainly due to the opposite porosity distribution of the porous magnesium oxide isolation layer used in the two. The porosity of the porous magnesium oxide isolation layer on the side close to the negative electrode in Application Example 1 is lower than the porosity on the side close to the solid electrolyte, which can prevent lithium ions from directly passing through the pores, effectively control the lithium ion transmission speed, and is more conducive to improving the coulombic efficiency and rate performance.
[0175] Compared with the liquid battery of Application Example 1, the rate performance of the battery made with the negative electrode assembly of Comparative Example 9 is reduced. This is because the height of the molten material above the porous magnesium oxide isolation layer in the negative electrode assembly is too high, which not only increases the amount of molten material used, but also leads to an increase in the lithium ion transmission path, thereby affecting the rate performance of the battery.
[0176] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A negative electrode assembly for a lithium metal battery, characterized in that: The negative electrode assembly includes a negative electrode, a composite transmission layer and a solid electrolyte arranged in sequence, the composite transmission layer includes a molten salt material, and a porous magnesium oxide isolation layer immersed in the molten salt material, and the porosity of the porous magnesium oxide isolation layer on the side close to the negative electrode is less than the porosity of the porous magnesium oxide isolation layer on the side close to the solid electrolyte.
2. The negative electrode assembly for a lithium metal battery according to claim 1, characterized in that: The average porosity of the porous magnesium oxide isolation layer is 30% to 40%.
3. The negative electrode assembly for a lithium metal battery according to claim 1 or 2, characterized in that: The porous magnesium oxide separation layer comprises a first separation layer and a second separation layer stacked in sequence, the first separation layer is connected to or close to the negative electrode, and the second separation layer is connected to or close to the solid electrolyte; The porosity of the first isolation layer is less than the porosity of the second isolation layer; Preferably, the thickness of the porous magnesium oxide isolation layer is 0.1 to 1 mm; Preferably, the thickness of the first isolation layer is ≤0.2 mm.
4. The negative electrode assembly for a lithium metal battery according to claim 1 or 2, characterized in that: The height of the molten salt material exceeding the porous magnesium oxide isolation layer is ≤0.1 mm; Preferably, the molten salt material includes lithium salt and bromine salt; Preferably, the molten salt material is a mixture of chlorine-containing lithium salt and bromine salt.
5. A method for preparing a negative electrode assembly for a lithium metal battery according to any one of claims 1 to 4, characterized in that: The preparation method comprises: A porous magnesium oxide isolation layer is prepared using magnesium oxide as a raw material, a molten salt material is covered on the surface of a solid electrolyte, the porous magnesium oxide isolation layer is immersed in the interior of the molten salt material, and then a negative electrode is arranged on the porous magnesium oxide isolation layer to obtain a negative electrode assembly.
6. The preparation method according to claim 5, characterized in that: The method for preparing the porous magnesium oxide isolation layer comprises: (1) Using a binder and a solvent to prepare a mixed colloid; (2) mixing the magnesium oxide powder and the mixed colloid in a first mass ratio to obtain a first mixed powder, and then mixing the magnesium oxide powder and the mixed colloid in a second mass ratio to obtain a second mixed powder, wherein the first mass ratio is less than the second mass ratio; (3) tableting the first mixed powder and sintering it once to obtain a magnesium oxide substrate; (4) coating the second mixed powder on the surface of the magnesium oxide substrate and performing secondary sintering to obtain a porous magnesium oxide isolation layer.
7. The preparation method according to claim 6, characterized in that: The preparation process of the mixed colloid includes: mixing a binder and a solvent, heating and stirring, cooling to room temperature after the binder is dissolved, and obtaining the mixed colloid; Preferably, the mass ratio of the binder to the solvent is 1:(12-18); Preferably, the binder comprises any one of polyvinyl alcohol, polyimide and sodium carboxymethyl cellulose or a combination of at least two thereof; Preferably, the temperature of the heating treatment is 80-90°C; Preferably, the stirring time is 1.5 to 4 hours.
8. The preparation method according to claim 6, characterized in that: The first mass ratio is (1.2-1.8):1; Preferably, the second mass ratio is (2-2.5):
1.
9. The preparation method according to claim 6, characterized in that: The tabletting pressure is 8-12 MPa; Preferably, the tabletting holding time is 300 to 480 seconds; Preferably, the temperatures of the primary sintering and the secondary sintering are independently 800-1000° C.; Preferably, the time for the primary sintering and the secondary sintering is independently 8 to 12 hours.
10. A liquid metal battery, characterized in that: The liquid metal battery includes a shell, in which a positive electrode region and a negative electrode region are arranged, the positive electrode region includes a positive electrode material, and the negative electrode region is provided with a negative electrode assembly for a lithium metal battery according to any one of claims 1 to 4, the solid electrolyte is arranged on a side close to the positive electrode region and is sealed with the inner cavity wall of the shell, and the operating temperature of the liquid metal battery is 200 to 400°C.